Clinical characteristics and oral manifestations of COVID-19: A cross-sectional study from Peshawar, Pakistan - Sana Hussain; Maryam Rauf; Saima Aleem; Khalid Rehman; Muhammad Amer Khan; Saad Liaqat; Nawshad Muhammad; Muhammad adnan Khan (Khyber Medical University Journal)
OBJECTIVES: To determine the prevalence of oral manifestations among PCR-confirmed COVID-19-positive patients and their potential correlations with age, gender, and systemic manifestations.